Current general guidelines in the treatment of insufficient pulmonary ventilation in patients without obstructive laryngeal injuries - Barani, Julio C; Irastorza, Juan F; Ferreira Ramos, Ney; Fonseca, Daniel; Alonso Regules, Justo E; Roncagliolo, A.; Gómez, L; Pérez Lagrave, A.; Núñez, C.; Rodríguez, A; et al. (Cirugía del Uruguay, 2020)
Presented at session 21th November 1956